Transjugular intrahepatic portosystemic stent shunt placement and embolization for hemorrhage associated with rupture of anorectal varices. Issue 4 (April 2018) - Wu, Xiuyan; Xuan, Wei; Song, Lei
Portal hypertension can lead to ectopic varices, which occur most frequently in the rectum. Rectal variceal bleeding in patients with portal hypertension is rare but can be life-threatening if not diagnosed and treated in a timely manner. However, no specific treatment guidelines have been established for rectal variceal bleeding. We herein report a case involving a woman with portal hypertension due to autoimmune liver disease who was successfully treated with a transjugular intrahepatic portosystemic stent shunt and variceal embolization. We recommend treatment of refractory ectopic variceal bleeding with a transjugular intrahepatic portosystemic stent shunt in combination with embolization.